2018
DOI: 10.1002/dmrr.3091
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates renal medullary hypoxia in diabetic nephropathy through inhibition uncoupling protein‐2

Abstract: Background The purpose of the study is to examine the effect of metformin on oxygen metabolism and mitochondrial function in the kidney of an animal model of insulinopenic diabetes in order to isolate any renoprotective effect from any concomitant effect on blood glucose homeostasis. Methods Sprague‐Dawley rats were injected with streptozotocin (STZ) (50 mg kg−1) and when stable started on metformin treatment (250 mg kg−1) in the drinking water. Rats were prepared for in vivo measurements 25 to 30 days after S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The therapeutic effects of metformin on slowing the progression of DN have been another spotlight apart from its hypoglycemic effects [28][29][30]. An initial objective of the study was to investigate the effect of metformin on TIF because it is still controversial [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic effects of metformin on slowing the progression of DN have been another spotlight apart from its hypoglycemic effects [28][29][30]. An initial objective of the study was to investigate the effect of metformin on TIF because it is still controversial [31].…”
Section: Discussionmentioning
confidence: 99%
“…As well known, DN was characterized by the development of tubulointerstitial brosis (TIF) and impaired renal function [7][8][9]. Evidence proved that RTECs underwent EMT during DN, leading to the over deposition of ECM after injury and further deterioration of TIF [10][11][12].…”
Section: Introductionmentioning
confidence: 97%
“…Metformin can overcome hyperglycemia-induced insulin resistance in podocytes by promoting the expression and function of SIRT1 and AMPK [103]. Furthermore, metformin attenuates DMinduced renal medullary tissue hypoxia by inhibiting uncoupling protein 2 in insulinopenic type 1 diabetes rats [104]. As mentioned above, metformin also modulates the interplay between oxidative stress, lipotoxicity, fibrosis, and aging in DKD to delay renal exacerbation.…”
Section: Dkdmentioning
confidence: 96%
“…They also found that metformin reduced the ATP production and oxygen consumption rates and increased cellular oxygen tension in T2D rats [ 62 ]. Christensen et al showed that metformin improves medullary hypoxia and attenuates mitochondrial superoxide radical production by inhibiting uncoupling protein-(UCP) 2 under diabetic conditions [ 69 ]. Senescence of renal cells has been implicated in the pathogenesis of DKD [ 70 ].…”
Section: Basic Mechanisms Underlying the Effects Of Metformin On Dmentioning
confidence: 99%